2022
DOI: 10.1186/s12951-022-01689-y
|View full text |Cite
|
Sign up to set email alerts
|

Combination of polythyleneimine regulating autophagy prodrug and Mdr1 siRNA for tumor multidrug resistance

Abstract: Multidrug resistance (MDR) has been restricting the efficacy of chemotherapy, which mainly include pump resistance and non-pump resistance. In order to fight overall MDR, a novel targeted gene/drug co-deliver nano system is developed, which can suppress the drug efflux pumps and modulate autophagy to overcoming both pump and non-pump resistance. Here, small interfere RNA (siRNA) is incorporated into polymer-drug conjugates (PEI-PTX, PP) which are composed of polyethyleneimine (PEI) and paclitaxel (PTX) via cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…CBN2 with siPHB1 displayed a stronger cytotoxic effect with a 21.3% cell survival rate after incubation with A549 cells for 48 h, suggesting that CPT and siPHB1 were released efficiently from CBN2 /siPHB1. However, the cell viability exhibited a slight increase beyond a certain mass ratio, potentially due to a delicate equilibrium of two factors: the elevated concentrations of CBN2 and its overexcessive condensation of siPHB1, CBN1 , and CBN3 were similar to that of CBN2 . , The results showed that CBN2 with 9 carbon alkyl chain is more suitable for codelivery CPT and siPHB1 in antitumor studies among the three amphiphilic liposomes.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…CBN2 with siPHB1 displayed a stronger cytotoxic effect with a 21.3% cell survival rate after incubation with A549 cells for 48 h, suggesting that CPT and siPHB1 were released efficiently from CBN2 /siPHB1. However, the cell viability exhibited a slight increase beyond a certain mass ratio, potentially due to a delicate equilibrium of two factors: the elevated concentrations of CBN2 and its overexcessive condensation of siPHB1, CBN1 , and CBN3 were similar to that of CBN2 . , The results showed that CBN2 with 9 carbon alkyl chain is more suitable for codelivery CPT and siPHB1 in antitumor studies among the three amphiphilic liposomes.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, combinations of genes and drugs have provided an exciting strategy for lung cancer treatment. Various modifications of nanocarriers have been proposed to deliver the anticancer siRNA and drugs. Wang et al developed a gene/drug codelivery system (PP/siRNA/HA) for delivery of Mdr1 siRNA and the chemotherapeutic agent paclitaxel (PTX) to synergistically inhibit the growth of Taxol-resistant lung cancer cells (A549/T) . Yu et al developed pH-responsive codelivery systems based on carbon dots modified with poly ethylenimine (PEI) and loaded siMRP1 and DOX, which showed enhanced therapeutic efficiency for lung cancer …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small interfering RNAs (siRNA) as inhibition for ABC drug efflux pumps were also tested in patients [283,284]. A boost in RNA interference (RNAi) based cancer bioenergetics modulation was observed using nanoplatforms as targeting systems [285,286]. Doxorubicin packed in polyelectrolyte nanoliposomes with Pyruvate kinase muscle isozyme-M2 (PKM2) siRNA reduced oxidative glycolysis, inhibited drug efflux pumps, induced ROS generation, and apoptotic cancer cell death [287].…”
Section: Targeting Tumor Bioenergetics and Resistant Niches Through N...mentioning
confidence: 99%
“…Alternatively, gene regulation techniques would provide a direct path to efficiently manipulate ABC transporters. For example, RNA interference (RNAi) technology that uses small interfering RNA (siRNA) has been widely used to inhibit disease-causing genes with complementary nucleotide sequences by degrading mRNA after transcription. However, the siRNA approach is not only a temporal way to lower the mRNA level of ABC transporters but requires continuous drug administration to continuously downregulate the target genes. Recent advances in the CRISPR-Cas9 system have abled therapeutic applications in human diseases with broad targeting scope and specificity. , With the in-depth study of the mechanisms of MDR, the CRISPR/Cas9 system has also been applied to revert resistance gene mutations and resensitize tumor cells to the treatment. However, most of the studies remain stalled on the determination of cytotoxicity in vitro, and the related analysis about reversing the MDR effect in vivo is still insufficient. One of the main reasons is the off-target effect of CRISPR/Cas9 gene editing.…”
mentioning
confidence: 99%